2006
DOI: 10.1159/000091480
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cholestasis and Cholangitis Induced by Biliary Drainage and Infusion in the Rat

Abstract: To develop a rat model of ascending cholangitis, we constructed a controllable and accessible biliary drainage and infusion system. We first modified a reversible cholestasis model of the rat and then induced ascending cholangitis by administration of Escherichia coli into the proximal choledochostomy tube. After biliary infusion of E. coli, the liver, choledochostomy tube and bile were all positive for E. coli, but no bacteria grew in rats receiving biliary infusion of normal saline. Retrograde cholangiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…In the current era, when NAC or conversion surgery after effective chemotherapy has been gaining wider acceptance, the basic research for investigating various effects of resolved OS on subsequent chemotherapy and/or surgery is considered very important. Hence, we attempted to acquire previously reported techniques for reversible OJ animal models (16,17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our group has reported the results of several studies using various animal hepatectomy and/or liver transplantation models (31)(32)(33)(34)(35)(36)(37)(38)(39)(40); thus, we recognized that our group has sufficient skill to reproduce these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current era, when NAC or conversion surgery after effective chemotherapy has been gaining wider acceptance, the basic research for investigating various effects of resolved OS on subsequent chemotherapy and/or surgery is considered very important. Hence, we attempted to acquire previously reported techniques for reversible OJ animal models (16,17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our group has reported the results of several studies using various animal hepatectomy and/or liver transplantation models (31)(32)(33)(34)(35)(36)(37)(38)(39)(40); thus, we recognized that our group has sufficient skill to reproduce these models.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on rat models of reversible OJ exist (16,17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The reports emphasized the simplicity of their methods.…”
mentioning
confidence: 99%
“…An ideal model for OJ and its reversal should be technically easy, stable during the study period, and associated with low mortality and morbidity rates. There already have been various kinds of methods for inducing and releasing OJ in rats, such as subcutaneously tunneled cannulation technique and tube-to-tube choledochocholedochostomy and choledochoduodenostomy [567]. However, they more or less have their own defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, they more or less have their own defects. It was reported that tube dislodgement and blockage were common disadvantages of cannulation techniques, and the technical complexity and high mortality and morbidity rates were common disadvantages of diverting techniques [56789]. These defects may limit the use of these models and influence the reliability of experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Intrahepatic cholestasis induced by ANIT is a convenient model for studies of hepatocyte injury and compensatory mechanisms in www.intechopen.com spontaneous recovery of liver function. Changes in hepatocyte transport proteins and dysregulation of bile secretion were revealed in mice with experimental cholestasis (Hsien et al, 2006). Cholestasis in mice and rats was observed in the early period after ANIT treatment (4-8 h), reaching maximum 24 and 48 h after ANIT administration.…”
Section: Anit As a Model Of Intrahepatic Cholestasismentioning
confidence: 99%